2011
DOI: 10.1159/000334194
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Involved-Field Conformal Radiotherapy for Cervical and Upper-Thoracic Esophageal Cancer

Abstract: Background: The aim of this study was to investigate the feasibility of involved-field irradiation (IFI) for the treatment of cervical and upper-thoracic esophageal cancer with concurrent chemoradiation. Patients and Methods: 102 eligible patients with cervical or upper-thoracic esophageal cancer were treated with concurrent chemoradiation and randomized to either an IFI or elective nodal irradiation (ENI) group. Results: Adverse events included infection (27.4 vs. 64.7%) and nausea (25.4 vs. 54.9%), with a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 13 publications
0
51
1
9
Order By: Relevance
“…Zhao et al 8 reported rates of grade 3 acute and late toxicities of 9% and 6% respectively after ifi, and no patients experienced acute or late grade 4 or 5 toxicities. Ma et al 21 reported significant differences between ifi and eni groups with respect to hematologic toxicity, infection, and vomiting. Those results appear promising, because treatment-related toxicities were less severe than those observed in trials using an extended field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al 8 reported rates of grade 3 acute and late toxicities of 9% and 6% respectively after ifi, and no patients experienced acute or late grade 4 or 5 toxicities. Ma et al 21 reported significant differences between ifi and eni groups with respect to hematologic toxicity, infection, and vomiting. Those results appear promising, because treatment-related toxicities were less severe than those observed in trials using an extended field.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the rationale for use of eni is to prevent regional nodal relapse rather than to improve survival. In a prospective randomized trial, Ma et al 21 compared eni with ifi in patients with cervical and upper thoracic eca, observing no significant difference in the 3-year os or locoregional control rate between the ifi and eni groups (32.0% and 80.1% vs. 41.3% and 85.7% respectively). Liu et al 22 noted that out-of-field regional cervical node metastasis occurred in 8% of the ifi group and 10% of the eni group in patients with cervical and upper thoracic eca.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from esophageal squamous cell cancer has generated controversy regarding the effectiveness of an expanded CTV in preventing either local recurrence or LNM, and it is unclear whether such large and standardized fields are always necessary, including for esophageal adenocarcinomas [7][8][9]. A more tailored CTV limited to nodal stations at significant risk could reduce adverse effects of RT, but data are lacking to guide the choice of which lymph node regions to include, particularly for distal esophageal adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain studies demonstrated that, in patients who underwent radiotherapy rather than ENI, the lymph node recurrence rate outside the field was 2-8% (7,8). A number of studies in China and abroad also demonstrated that, compared with ENI, the toxicity of which was considered acceptable for the majority of the patients, the recurrence rate and distant metastasis in patients treated with IFI was not notably increased (4,13,14). Therefore, regarding patients treated with IFI, it remains unclear how they should be irradiated in order to control the recurrence of regional lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, an increasing number of studies have been conducted on elective nodal irradiation (ENI) for esophageal cancer; however, their conclusions have been inconsistent. It was previously reported that, compared with involved-field irradiation (IFI), ENI does not improve the local control rate or long-term survival of patients with esophageal cancer (4). Previous studies have indicated that ENI may prevent regional lymph node metastasis (5,6), whereas other studies (7)(8)(9) reported that the isolate out-of-field nodal failure rate was low and overall survival did not decrease when IFI was used (6,7).…”
Section: Introductionmentioning
confidence: 99%